ANALISIS KONDISI THE LAW OF DIMINISHING RETURN PADA SUB SEKTOR PERIKANAN LAUT DI PROVINSI BANTEN TAHUN 2007-2014 - Suharto, Umayatu Suiroh; Khalindra, Dimas (Jurnal Ekonomi-Qu, 2017)
This analysis aims to explain empirically about the condition of The Law of Diminishing Return (LDR). The condition of LDR is a condition that is theoretically present in explanation description about production analysis with two variables, that is production variable (Q) with variable of worker input (L). The results of this analysis indicate that the input L (ie Fisherman) does not affect the Q (ie Product), which is indicated by the value of t count is smaller than its table value. And the nature on the relationship between Fisherman's variable to Product is negative, it explains that the addition of Fisherman variable number will cause a decrease in product value. These results explain the presence of LDR conditions in the analysis model.Keywords: Production Function, Law f Diminishing Return, Fisherman, Product.